Studies on the Characterisation of Agriculture Waste (Banana Pseudo Stem) for Bioethanol Yield Production. - Nurul Husna, Abdul Rashid (2016)
A research has been investigated to further the production of bioethanol from banana especially from its stem. In this study, banana pseudo stem before and after pre-treatment were characterised by their crystallinity index and amorphous by using X-RD. Banana pseudo stem was treated with alkaline pre-treatment by using Sodium Hydroxide to study the effect of pre-treatment and the bioethanol production of untreated and treated banana pseudo stem was detected by HPLC. It was found that, untreated banana pseudo stem has higher crystallinity index (CI) than treated banana pseudo stem. In addition, the X-RD result for untreated banana pseudo stem also showed the higher concentration that is 44.5% compared to treated samples which is 22%. So, untreated banana pseudo stem was proved effective in enhancing the ethanol production rather than treated banana pseudo stem except the pre-treatment have to undergo properly.